Differences in blood creatinine levels using mono reagent which was checked immediately and which was delayed for 5 hours at room temperature - Nurhidayati Nurhidayati; Ratih Hardisari; Anik Nuryati (PUINOVAKESMAS, 2021)
Reagents used for examination must be considered for stability. Reagents made beforehand must be used immediately because the reagent that has been opened has a shorter stability period than the reagent that has not been opened. This study aims to determine the difference in creatinine levels using a mono reagent that is immediately used and which is left in for 5 hours at room temperature. This research is a pre-experimental study with a one-group pretest-posttest research design. The research sample was the remaining serum of the patients who were examined in the laboratory of Medika Sangatta Hospital as many as 40 samples. The test results were analyzed descriptively and statistically using paired sample t-test. The results of the descriptive test showed that the difference between the mean creatinine levels using immediate reagent and those experiencing indentation for 5 hours was 0.1 with the maximum value of creatinine levels using immediate reagent and those experiencing indwelling were 1.7 mg/dl and 1.6 mg/dl. While the minimum values ??are 0.9 mg / dl and 0.8 mg / dl (p=0.003). There was a difference in creatinine levels using a mono reagent which is immediately used and which has been left standing for 5 hours at room temperature so the mono reagent that has been made should be used immediately.